Relationship Between Sustainable Development Practices And Financial And Non-Financial Performance In Jordanian Construction Industry : Role Of Transformational Leadership As A Moderator - Jundi, Khaled Abdel Qader Saleh (2021)
This study examines the direct relationship between sustainable development practices (SDPs) and financial and non-financial performance. The study also examines the moderating effect of transformational leadership (TL) on the relationship between sustainable development practices and financial and non-financial performance. With the use of primary data sources, this study focusses on the Jordanian construction industry.